Aktivitas Antibakteri dari Ekstrak Etanol Ganoderma sp. Asal Pulau Lombok - Adelina Oktaviani; Aida Muspiah; Faturrahman Faturrahman (LPPM Universitas Mataram, 2020)
The use of antibiotics that are not according to the rules and antibiotics in the long term can cause resistance to bacteria. This study aims to determine the presence of antibacterial activity and the effect of increasing the concentration of ethanol extract of Ganoderma sp. against several test bacteria. Extract from Ganoderma sp. obtained by maceration method using ethanol 95% solvent. The extract concentrations used were 20%, 40%, 60% and 80%. This research was conducted using the wells method with ciprofloxacin as a positive control and 50% DMSO as a negative control. The parameter measured is the large diameter of the inhibition formed around the well. The results of the antibacterial activity test of ethanol extract Ganoderma sp. has greater inhibitory activity against gram-negative bacteria. The inhibitory activity of ethanolic extract of Ganoderma sp. on the growth of test bacteria increased with increasing concentration of the extract